Place and space in Sámi education - Keskitalo, Pigga (Policy Futures in Education, 2019)
This article considers the Sa ´mi understanding of time and place in pedagogical settings. The study is based on research material gathered at Sa ´mi schools and from teaching conducted in the Sa ´mi language. These data were combined to develop a theoretical review of teacher education from a metatheoretical perspective. The research challenges schools’ pedagogical arrangements. Local contents of the study are an important part of the school syllabus, and this article suggests that they are closely tied to school educational arrangements. This study also suggests that, in Northern schools, the Sa ´mi worldview and traditional knowledge should be closely connected to school practices. This means that the Sa ´mi understanding of time and place should receive sufficient emphasis in school curricula. Schools could benefit from the open learning concept, such as modern curricula grounded in teaching that is phenomenon based. This could increase pupils’ motivation and sense of connection to the local area. With mediating structures – connected to multicultural educational contexts – such educational systems could be developed.